A Study of Learning Achievement and Analytical Reading Ability on Ramayana Unit of Grade 8 Students Using SQ6R Method with Board Games - Putta, Nattapong; Jongkonklang, Sirinat (Ratchaphruek Journal, 2025)
This experimental research was a study of using the SQ6R method with board games. It aimed to: 1) Compare the learning achievement on Ramayana Unit before and after and compare posttest score of learning achievement with the designated criterion 70; and 2) Compare the analytical reading ability before and after using the SQ6R method with board games. The sample consisted of 40 grade 8/4 students from Bunlua Wittayanusorn School. The sample was selected using cluster random sampling. The experimental tools included four instructional plans based on the SQ6R method with board games. Data collection instruments were the multiple choice learning achievement test, and an analytical reading ability test. Data were analyzed using mean, standard deviation, percentage, and t-test. The study revealed that 1) The learning achievement on Ramayana Unit was significantly higher than before, and Posttest score higher than the 70 percent criterion with the statistics significance at the .05 level. and 2) Analytical reading ability was significantly higher than before with the statistics significance at the .05 level.